Effect of spacing and pruning on growth, yield and economics of long melon (Cucumis melo var. utilissimus) under naturally ventilated polyhouse - SINGH, AWANI KUMAR; SABIR, NAVED; JAT, GOGRAJ SINGH; SINGH, JOGENDRA; SINGH, VEERPAL; SINGH, AJEET; KUMAR, ANIL; KUMAR, JUGENDRA (The Indian Journal of Agricultural Sciences, 2021)
The present experiment was conducted in naturally ventilated polyhouse structure at CPCT, ICAR-IARI, New Delhi for off-season cultivation of long melon (Cucumis melo var. utilissimus) during 2016 and 2017 under five plant spacing and five branch pruning methods. Plant spacing and pruning methods revealed significant positive influence on yield and net return. Fruit yield decreased with increasing plant spacing and it was found maximum in closer spacing of 50 cm × 20 cm. The net return and B:C ratio also followed similar trends. Among different pruning methods, node branch pruning method (P3) gave highest yield (76.35 q/1000m2) with maximum net return of ₹ 81020/1000m2 and BC ratio 1:1.36 compared to other pruning intensity or no pruning (control). Pruning method involving three nodes per branch was statistically at par in net return and BC ratio with two-nodes per branch method. Study showed that off-season cultivation of long melon under polyhouse structure is a good option to farmers for generating more income and employment.